Generating Regional-Scale Improvements in SME Corporate Responsibility Performance: Lessons from Responsibility Northwest - Roberts, Sarah (Journal of business ethics, 2006)
This paper describes the research carried out into small and medium enterprises (SMEs) and corporate responsibility (CR) in the Northwest of England during Phase I of Responsibility Northwest, a partnership programme designed to significantly increase the CR of the region. By engaging with significant numbers of SMEs and SME support providers across the region, key insights were gained in three key areas: , The current attitudes to, understanding of, and management of CR issues in the SME sector., The barriers to greater implementation of CR management., The opportunities for overcoming the barriers and improving regional CR., The research revealed a large diversity both in terms of understanding of the issues and their management. Seven key barriers to improve CR performance were identified which centred round the inappropriateness and inaccessibility of current CR approaches and support services on CR, certain characteristics of SMEs which tend to reduce their interest and opportunities for engaging in CR activities and supply-chain barriers. Fortunately there was significant agreement on the mechanisms which should be used to overcome these barriers, in particular the importance of delivering CR support through existing business networks that are valued and trusted by SMEs. These results have been used to create the partnership programme, Responsibility Northwest Phase II that runs until 2008 and aims to significantly increase the overall CR of Northwest England.